Bivalent non-typhoidal Salmonella outer membrane vesicles immunized mice sera confer passive protection against gastroenteritis in a suckling mice model. Issue 2 (8th January 2021) - Maiti, Suhrid; Howlader, Debaki Ranjan; Halder, Prolay; Bhaumik, Ushasi; Dutta, Moumita; Dutta, Shanta; Koley, Hemanta
Highlights: Immunization with BINTSOMVs immunogen induces adaptive immune response in adult mice. iNTS can colonize naturally in 1-day old suckling mice upon oral infection. Upon oral iNTS infection 1-day old suckling mice developed gastroenteritis naturally. BINTSOMVs immunized adult mice serum can reduce iNTS mediated gastroenteritis. BINTSOMVs immunized adult serum also protect suckling mice from iNTS infection. Abstract: Invasive non-typhoidal Salmonella (iNTS) serovars, especially Salmonella Typhimurium (ST) and Salmonella Enteritidis (SE), cause gastroenteritis worldwide. Due to the emergence of multi-drug resistance in iNTS, a broad-spectrum vaccine is urgently needed for the prevention of iNTS infection. Currently, there is no effective licensed vaccine against iNTS available in the market. We have formulated an outer membrane vesicles (OMVs) based bivalent immunogen as a vaccine candidate to generate broad-spectrum protective immunity against both recently circulating prevalent ST and SE . We have isolated OMVs from ST and SE and formulated the immunogen by mixing both OMVs (1:1 ratio). Three doses of bivalent immunogen significantly induced humoral immune responses against lipopolysaccharides (LPSs) and outer membrane proteins (OMPs) as well as a cell-mediated immune response in adult mice. We also observed that proteins of OMVs act as an adjuvant for generation of high levels of anti-LPS antibodies through T cell activation. We then characterized the one-day old suckling mice model for both ST and SE mediated gastroenteritis and used the model for a passive protection study. In the passive protection study, we found the passive transfer of bivalent OMVs immunized sera significantly reduced ST and SE mediated colonization and gastroenteritis symptoms in the colon of suckling mice compared to non-immunized sera recipients. The overall study demonstrated that OMVs based bivalent vaccine could generate broad-spectrum immunity against prevalent iNTS mediated gastroenteritis. This study also established the suckling mice model as a suitable animal model for vaccine study against iNTS mediated gastroenteritis.